Importance of Clinical Judgment Skill Competencies Across Practice Settings: Certified Rehabilitation Counselors' Perceptions. - Austin, Bryan S.; Lee, Chun-Lung; McCarthy, Amanda; Sprong, Matthew (Journal of Applied Rehabilitation Counseling, 2023)
Accurate clinical judgments are critically important for counselors in their work with clients. To date, there are no studies that have assessed rehabilitation counselors' knowledge of clinical judgment and its importance to implement in practice. In this internet-based study, a random sample of certified rehabilitation counselors (CRCs; n = 579) were surveyed using the clinical judgment skill inventory (CJSI). The CJSI measures clinical judgment skills across seven clinical judgment skill areas (scientific attitude, cognitive complexity, cultural bias, confirmatory bias, memory bias, negative bias, and evidence-based practice). CRC participants overall rated clinical judgment skills to be important. Significant multivariate analysis of variance (MANOVA) test indicated significant mean differences between practice settings (Wilks' Lambda F = 3.31, p value <.01) in "scientific attitude" (F -statistic = 3.91, p value <.01), "cultural bias" (F -statistic = 3.71, p value <.01), "confirmatory bias" (F -statistic = 3.02, p value =.01), and "evidence-based practice" (F -statistic = 5.62, p value <.01). Specifically, CRCs working for a college or university perceived clinical judgment skill areas to be more important than CRCs working in other practice settings. Implications for rehabilitation counseling practice are discussed.